La Descontextualización De Las Tareas Escolares Y Su Incidencia En Los Aprendizajes De Los Estudiantes De La Escuela Francisco Piana Rattó De La Ciudad De Babahoyo Provincia Los Ríos. - Solis Martinez, Isaura (2015)
The research was conducted in the School of Basic Education Basic Education Unit Francisco Piana Ratto of the parish of Camilo Ponce of the City of Babahoyo province of The River, knowledge of teachers was analyzed on the contextualization of education and assessment of parents about performance of their children with homework, finding that most parents or guardians live with their children, they are satisfied with the performance of their constituents, this contradicts the statement with a teacher who in his most indicated that they disagree with the performance of their students. Parents or guardians do not attend regularly to check the status of your child's education; they also do not check daily homework of their children. Students use three and more than three hours a day on homework at home, time spent to understand and seek methods of performing the task sent. The tasks students are not adequately supervised by teachers or by parents. There is ignorance on the part of parents that beneficiary use internet on schoolwork. This shows the need for the Education Unit has a laboratory computer with internet access.